2003
DOI: 10.1002/ssu.10042
|View full text |Cite
|
Sign up to set email alerts
|

Gastrectomy, peritonectomy, and perioperative intraperitoneal chemotherapy: The evolution of treatment strategies for advanced gastric cancer

Abstract: Gastric cancer disseminates by hematogenous, lymphatic, and transcoelomic routes. For maximal containment of the malignant process, perioperative intraperitoneal chemotherapy is necessary in two groups of patients in whom the primary cancer can be resected. Those patients who have been resected for cure and have a high likelihood of microscopic residual disease require intraperitoneal chemotherapy. This includes all T3 and T4 patients, and patients with N2 nodes present. A series of randomized and nonrandomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
1
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 44 publications
2
86
1
9
Order By: Relevance
“…Peritoneal recurrence after a curative resection for gastric cancer is thought to originate from intraperitoneal free cancer cells (IFCC), which in turn arise from two potential sources: spontaneous exfoliation of cancer cells from the primary tumor from the serosal surface, and iatrogenic dissemination of cancer cells as a result of the surgical trauma [26,29]. Sugarbaker et al proposed the Btumor cell entrapment hypothesis^ [26], according to which the IFCC adhere to the surgical raw area within minutes-a process facilitated by fibrin entrapment and assisted by cytokines released as part of the wound healing mechanism.…”
Section: Rationale For Hipecmentioning
confidence: 99%
See 2 more Smart Citations
“…Peritoneal recurrence after a curative resection for gastric cancer is thought to originate from intraperitoneal free cancer cells (IFCC), which in turn arise from two potential sources: spontaneous exfoliation of cancer cells from the primary tumor from the serosal surface, and iatrogenic dissemination of cancer cells as a result of the surgical trauma [26,29]. Sugarbaker et al proposed the Btumor cell entrapment hypothesis^ [26], according to which the IFCC adhere to the surgical raw area within minutes-a process facilitated by fibrin entrapment and assisted by cytokines released as part of the wound healing mechanism.…”
Section: Rationale For Hipecmentioning
confidence: 99%
“…Sugarbaker et al proposed the Btumor cell entrapment hypothesis^ [26], according to which the IFCC adhere to the surgical raw area within minutes-a process facilitated by fibrin entrapment and assisted by cytokines released as part of the wound healing mechanism. This hypoxic environment renders the trapped cancer cells relatively immune to the effects of systemic chemotherapy.…”
Section: Rationale For Hipecmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Japan, the early research with peritoneal carcinomatosis from gastric primary, utilizing combination treatment with etoposide, mitomycin C, and cisplatin, has been reported [37,38]. Limited but definite benefits were demonstrated when palliative gastrectomy was combined with intraperitoneal heated multidrug treatment in gastric cancer patients with limited peritoneal seeding [8].…”
Section: Etoposidementioning
confidence: 99%
“…Eight different phase III studies reported a survival advantage when perioperative intraperitoneal chemotherapy is added to surgery in patients with primary gastric cancer. Stage III patients projected the greatest survival advantage [8]. Although benefits have been reported in the literature, a standardization of the optimal management plans for prevention or treatment of peritoneal surface malignancy has not been developed.…”
Section: Introductionmentioning
confidence: 99%